2010
DOI: 10.1111/j.1469-1795.2010.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating physiology into conservation: an approach to help guide translocations of a rare reptile in a warming environment

Abstract: The physiology of an animal determines the range of environmental conditions under which it can survive. Surprisingly, relatively few conservation studies have used physiology to make predictions about the performances of translocated individuals in their new environment. Tuatara Sphenodon punctatus are of international significance as the last rhynchocephalian reptile. Natural populations are now restricted to $30 offshore islands in northern New Zealand, where survival of at least one population is threatene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 50 publications
(56 reference statements)
0
23
2
Order By: Relevance
“…The tuatara preferred body temperature is in the range 19.5°-23.rC (Besson and Cree 2011), but recordings of ambient temperatures in our study indicated that this preferred body temperature could be achieved within the shaded forest in only one of the three years studied. Fairy prions enable tuatara to maintain a higher body temperature through the night for several months of the year, October to January (austral spring to summer).…”
Section: Discussioncontrasting
confidence: 55%
“…The tuatara preferred body temperature is in the range 19.5°-23.rC (Besson and Cree 2011), but recordings of ambient temperatures in our study indicated that this preferred body temperature could be achieved within the shaded forest in only one of the three years studied. Fairy prions enable tuatara to maintain a higher body temperature through the night for several months of the year, October to January (austral spring to summer).…”
Section: Discussioncontrasting
confidence: 55%
“…In species of Woodworthia and other geckos, and regardless of sex, increased T b has many physiological benefits including increased growth rate (Autumn & De Nardo, ; Angilletta, ), faster prey capture, handling and digestion (Besson & Cree, ) and faster sprint speed (Gaby et al ., ). In lizards generally, basking may also facilitate fast re‐growth of the tail after autotomy – a considerable advantage as tail loss is detrimental both socially and physiologically (Fox & Rostker, ; Bateman & Fleming, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the conservation context, if the focal populations are not exchangeable, numerical enhancement or translocations of individuals across sites can be counterproductive (Hey et al . ; Besson & Cree ) or opportunities for genetic rescue can be overlooked (Beauclerc et al . ; Huff et al .…”
Section: Introductionmentioning
confidence: 99%
“…Most obviously, species delimitation can be inaccurate and lead to misleading phylogenetic hypotheses or mistaken assessments of the importance of particular supposed isolating mechanisms (Bickford et al 2007;Rittmeyer & Austin 2012). In the conservation context, if the focal populations are not exchangeable, numerical enhancement or translocations of individuals across sites can be counterproductive (Hey et al 2005;Besson & Cree 2011) or opportunities for genetic rescue can be overlooked (Beauclerc et al 2009;Huff et al 2011).…”
Section: Introductionmentioning
confidence: 99%